Dual targeting of BCMA and SLAMF7 with the CARtein system: chimeric antigen receptors with intein-mediated splicing elicit specific T cell activation against multiple myeloma - Moares, Noelia; Gonzalez-Garcia, Pablo; Yi-He, Wenjie; Muñoz-Miranda, Juan P.; Gabucio, Antonio; Luna-Espejo, Rosa; Ocaña-Cuesta, Javier; Fernandez-Cisnal, Ricardo; Fernandez-Ponce, Cecilia M.; Garcia-Cozar, Francisco (Frontiers in Immunology, 2025)
IntroductionChimeric antigen receptor (CAR) T-cell therapy has demonstrated remarkable efficacy against multiple myeloma (MM). However, several barriers continue to limit the overall effectiveness of this approach, such as high production costs, prolonged manufacturing timelines, safety issues, and the potential for tumor antigen escape due to selective therapeutic pressure. To overcome these challenges, innovative CAR T strategies, such as engineering modular CAR systems, are being explored. These systems utilize adaptor molecules to enable multi-antigen targeting, thereby enhancing specificity, safety, and overall efficiency of CAR T-cell therapy. Notably, CAR T-cells directed against BCMA and SLAMF7 antigens have generated strong and robust antitumor responses in MM therapy.MethodsTo address the limitations of conventional CAR T therapy, we developed a novel modular CAR platform targeted against BCMA and SLAMF7. This was achieved using a split intein-mediated protein splicing mechanism, which allows specific covalent peptide bonds to form between CAR modules. This strategy maintains an almost seamless CAR structure, preserving its overall integrity and functionality. The design of the intein-spliced CAR system (termed "CARtein") was further optimized through advanced protein structure prediction software.ResultsCells expressing the spliced CARtein constructs, engineered to target BCMA, SLAMF7, or both antigens simultaneously, demonstrated robust and highly specific activation in response to their respective antigens.DiscussionThese results suggest that the CARtein platform is a promising, versatile, and highly specific approach for the modular design and engineering of CARs, enabling multi-antigen targeting while maintaining structural and functional integrity. This modular strategy addresses key limitations of conventional CAR T-cell therapy and may improve both the safety and effectiveness of future MM treatments.